A Leadership and Managerial Competency Framework for Public Hospital Managers in Vietnam - Phan Van Tuong; Nguyen Duc Thanh (AIMS Press, 2017)
Objective: The aim of this paper was to develop a leadership and managerial competency framework for public hospital managers in Vietnam. Methods: This mixed-method study used a four-step approach. The first step was a position description content analysis to identify the tasks hospital managers are required to carry out. The resulting data were used to identify the leadership and managerial competency factors and items in the second step. In the third step, a workshop was organized to reach consensus about the validity of these competency factors and items. Finally, a quantitative survey was conducted across a sample of 891 hospital managers who are working in the selected hospitals in seven geographical regions in Vietnam to validate the competency scales using exploratory factor analysis (EFA) and Cronbach's alpha. Results: The study identified a number of tasks required for public hospital managers and confirmed the competencies for implementing these tasks effectively. Four dimensions with 14 components and 81 items of leadership and managerial competencies were identified. These components exhibited 83.8% of variance and Cronbach's alpha were at good level of 0.9. Conclusions: These competencies are required for public hospital managers which provide guidance to the further development of the competency-based training for the current management taskforce and preparing future hospital managers.